A Spiky Silver‐Iron Oxide Nanoparticle for Highly Efficient Targeted Photothermal Therapy and Multimodal Imaging of Thrombosis. Issue 11 (12th January 2023) - Vazquez‐Prada, Karla X.; Moonshi, Shehzahdi S.; Wu, Yuao; Akther, Fahima; Tse, Brian W.C.; Sokolowski, Kamil A.; Peter, Karlheinz; Wang, Xiaowei; Xu, Gordon; Ta, Hang Thu
Abstract: Thrombosis and its complications are responsible for 30% of annual deaths. Limitations of methods for diagnosing and treating thrombosis highlight the need for improvements. Agents that provide simultaneous diagnostic and therapeutic activities (theranostics) are paramount for an accurate diagnosis and rapid treatment. In this study, silver‐iron oxide nanoparticles (AgIONPs) are developed for highly efficient targeted photothermal therapy and imaging of thrombosis. Small iron oxide nanoparticles are employed as seeding agents for the generation of a new class of spiky silver nanoparticles with strong absorbance in the near‐infrared range. The AgIONPs are biofunctionalized with binding ligands for targeting thrombi. Photoacoustic and fluorescence imaging demonstrate the highly specific binding of AgIONPs to the thrombus when functionalized with a single chain antibody targeting activated platelets. Photothermal thrombolysis in vivo shows an increase in the temperature of thrombi and a full restoration of blood flow for targeted group but not in the non‐targeted group. Thrombolysis from targeted groups is significantly improved ( p < 0.0001) in comparison to the standard thrombolytic used in the clinic. Assays show no apparent side effects of AgIONPs. Altogether, this work suggests that AgIONPs are potential theranostic agents for thrombosis. Abstract : The novel spiky silver‐iron oxide nanoparticles (AgIONPs) is developed and performed as highly efficient thrombolytic agent. The antibody attached to the AgIONPs provides specific binding of the nanoparticles to thrombi, as shown by multimodal imaging using photoacoustic and fluorescence imaging. Upon 808 nm laser exposure, hyperthermia‐induced thrombolysis is achieved.